PENATAAN RUANG KANTOR DALAM MEWUJUDKAN EFISIENSI KERJA PEGAWAI PADA KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI SULAWESI TENGGARA - Loeth, Lidya Tri Wardhany; Amir, H. Muh; Tawai, Adrian (Universitas Halu Oleo, 2020)
This research is intended to know, Office Space Structuring In Realizing The Efficiency Of Employee Work at The Ragional Office Of The National Land Agency Of Southeast Sulawesi Province. The method of research used is qualitative research is descriptive, description of the observation of interviews and documentation studies, so as to describe various matters relating to, Office Space Arrangement In Realizing The Efficiency Of Work Staff At The Regional Office Of Natioal Land Agency of Southeast Sulawesi Province. Data that has been obtained is analyzed qualitatively and described in a descriptive form. The results showed that, The Office Space Arrangement In Realizing Employee Work Efficiency is reviewed from office work, activity series, health and satisfaction work, the arrangement of the workplace has been implemented according to the procedure even though it has not been perfect and maximal. Efficiency of personnel work can be seen from the sucess of effevtive, economical, and the implementation of accountable, in the implementation is still less good because of the lack of awareness of some employees to work efficiently.